Communicating the Gospel in a digital age : a case study of the Dioceses of Kampala and Namirembe in the Anglican Church of Uganda - Kitayimbwa, Lydia Nabunya Nsaale (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.